The argumentation of the students about plant biodiversity: Quasi-experimental research - Luthfiana Nurtamara; Sri Amintarti; Aulia Ajizah; Dewi Amelia Widiyastuti; Noorhidayati Noorhidayati; Amalia Rezeki (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Argumentation in science learning is crucial to form scientific explanations supported by strong claims with evidence and explanations. The study used two classes, namely the control class using the discovery learning model, using textbooks from the school, and the experimental group using the STEM PJBL learning model, assisted by teaching modules developed by researchers. The control class consisted of 35 students, and the experimental class consisted of 36 students. The research used a quasi-experimental research method with a posttest-only control design. Post-test results in the control group had an average of 24.28, and the experimental group 50.278. The statistical test used the Mann-Whitney U non-parametric test with a significance value of 0.000, which means that the P-value is less than the 0.05 significance level, so H0 is rejected, so there is a difference in value between the control class and the experimental class on argumentation skills. The results of this research conclude that most students at level 1 are only able to make claims without being supported by data and reasoning. The low level of argumentation is caused by the lack of argumentation training and the lack of conceptual understanding of students, so it is recommended that science teaching be given argumentation training with contextual and constructivist learning models.Abstrak. Argumentasi dalam pembelajaran sains sangat penting untuk membentuk argumentasi ilmiah yang didukung oleh klaim yang kuat dengan bukti dan penjelasan. Penelitian ini menggunakan dua kelas, yaitu kelas kontrol yang menggunakan model pembelajaran discovery learning dengan menggunakan buku teks dari sekolah, dan kelompok eksperimen yang menggunakan model pembelajaran STEM PJBL dibantu dengan modul pembelajaran yang dikembangkan oleh peneliti. Kelas kontrol terdiri dari 35 siswa dan kelas eksperimen terdiri dari 36 siswa. Penelitian ini menggunakan metode penelitian kuasi eksperimen dengan posttest-only control design. Hasil posttest pada kelompok kontrol memiliki rata-rata 24,28, dan kelompok eksperimen 50,278. Uji statistik yang dapat dilakukan adalah uji non parametrik Mann-Whitney U dengan nilai signifikansi 0,000 yang berarti nilai P-value lebih kecil dari taraf signifikansi 0,05, maka H0 ditolak, sehingga terdapat perbedaan nilai antara kelas kontrol dan kelas eksperimen pada keterampilan argumentasi. Hasil penelitian disimpulkan bahwa kebanyakan berada di level 1 sehingga peserta didik hanya mampu membuat claim tanpa disertai data dan alasannya. Rendahnya nilai argumentasi disebabkan karena kurangnya pelatihan berargumentasi dan kurangnya penguasan konsep peserta didik, sehingga diharapkan pembelajaran sains diberikan pelatihan berargumentasi dengan model pembelajaran kontekstual dan konstruktivis.